THE PERSPECTIVE OF PRIMARY SCHOOL TEACHERS IN TEACHING ENGLISH - Agustinus Triwinanta; Markus Budiraharjo (PROJECT (Professional Journal of English Education), 2022)
At this time the role of English is very important in all areas of human life, especially in the field of education. The education policy to introduce English at primary school age has been implemented. Many schools have included English as a local content subject in the school curriculum. And in learning the teacher uses English as the language of instruction "lingua franca". Therefore, this study aims to investigate how the learning process of an English teacher teaches English in primary schools and can contribute to an understanding of how elementary school teachers view English as one of the local content to equip students with English skills. The method used is a qualitative research method with data taken from interviews with 2 English teachers at private elementary schools in Sleman. The results obtained from this study are that teachers believe that the use of English can increase primary school students' interest in learning English but the perspectives and beliefs of each teacher are different. Keywords:  Primary School, English Language, Learning English